THE CONCEPT OF NOBLE CHARACTER EDUCATION IN THE PERSPECTIVE OF USTADZ ADI HIDAYAT: ITS RELEVANCE TO THE FORMATION OF MUSLIM CHARACTER IN THE DIGITAL ERA - Satra, Alihan; Wahyuni, Retno Tri; Muslimah, Mona; Fitriani, Dwi Okta; Ma’arif, Fahmi (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This article aims to examine in depth the concept of noble character education from the perspective of Ustadz Adi Hidayat and its relevance to the formation of Muslim character in the digital era. The background of this study stems from the growing moral crisis among younger generations, which demands a renewed approach to moral education based on Islamic values. This research employs a library research method by analyzing classical and contemporary literature, including Ustadz Adi Hidayat’s digital da’wah content. The findings reveal that noble character is a direct manifestation of strong Islamic creed (aqidah) and is inseparable from the formation of a Muslim’s personality. Ustadz Adi Hidayat emphasizes the importance of emulating the Prophet Muhammad’s morals—siddiq (truthfulness), amanah (trustworthiness), fathanah (intelligence), and tabligh (conveying the message)—as an integrative model of character education. These findings highlight that moral education rooted in correct faith, combined with the strategic use of digital media, offers a relevant solution for developing spiritually, morally, and socially strong Muslim generations. This study contributes conceptually to the development of an Islamic character education model that is responsive to contemporary challenges. Artikel ini bertujuan untuk mengkaji secara mendalam konsep pendidikan akhlak mulia dalam perspektif Ustadz Adi Hidayat serta relevansinya dalam pembentukan karakter Muslim di era digital. Latar belakang penelitian ini didasarkan pada meningkatnya krisis moral generasi muda yang menuntut pembaruan pendekatan pendidikan akhlak berbasis nilai-nilai Islam. Penelitian ini menggunakan metode studi pustaka (library research) dengan menganalisis literatur klasik dan kontemporer, termasuk konten dakwah digital Ustadz Adi Hidayat. Hasil penelitian menunjukkan bahwa akhlak mulia merupakan manifestasi langsung dari akidah yang kokoh dan tidak dapat dipisahkan dalam pembentukan kepribadian Muslim. Ustadz Adi Hidayat menekankan pentingnya meneladani akhlak Rasulullah SAW—siddiq, amanah, fathanah, dan tabligh—sebagai model pendidikan karakter yang integratif. Temuan ini menegaskan bahwa pendidikan akhlak yang ditopang oleh pemahaman akidah yang benar, ditambah dengan optimalisasi media digital, dapat menjadi solusi strategis dalam membentuk generasi Muslim yang unggul secara spiritual, moral, dan sosial. Penelitian ini memberikan kontribusi konseptual terhadap pengembangan model pendidikan karakter Islam yang relevan dengan tantangan zaman.